Oil price shocks and policy implications the emergence of U.S. tight oil production: a case study - Voth, Jeffrey Michael (2015)
How have shocks to supply and demand affected global oil prices; and what are key policy implications following the resurgence of oil production in the United States? Highlights: − The recent collapse in global oil prices was dominated by oversupply. − The future of tight oil in the United States is vulnerable to obstacles beyond oil prices. − Opinions on tight oil from the Top 25 think tank organizations are considered. Global oil prices have fallen more than fifty percent since mid-2014. While price corrections in the global oil markets resulted from multiple factors over the past twelve months, surging tight oil production from the United States was a key driver. Tight oil is considered an unconventional or transitional oil source due to its location in oil-bearing shale instead of conventional oil reservoirs. These qualities make tight oil production fundamentally different from regular crude, posing unique challenges. This case study examines these challenges and explores how shocks to supply and demand affect global oil prices while identifying important policy considerations. Analysis of existing evidence is supported by expert opinions from more than one hundred scholars from top-tier think tank organizations. Finally, implications for United States tight oil production as well as global ramifications of a new low price environment are explored.